2023
DOI: 10.3390/ijms24097956
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence and Skin: A State of Art of Its Etiopathogenetic Role and Crucial Watershed for Systemic Implications

Abstract: Immunosenescence is a complex multifactorial phenomenon consisting of wide-ranging remodeling of the immune system during the life span, resulting in an age-related qualitative–quantitative decline of immune cells and cytokines. A growing body of evidence in the international literature is highlighting the etiopathogenetic role of skin immunosenescence in the onset of various dermatologic conditions. Skin immunosenescence also serves as an interesting watershed for the onset of system-wide conditions in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 180 publications
0
8
0
Order By: Relevance
“…23 Whether xerosis in older people should be considered a disease or a part of the aging process is being debated, and some authors even describe xerosis as a low-grade atopic eczema. 24 Two methods are known for making artificial skin barrier-disrupted mouse models, namely, acetone application and tape-stripping. 19,21 Rissmann et al suggested that barrier disruption caused by acetone treatment is mainly caused by the removal of corneocytes, and it is also observed by tape-stripping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Whether xerosis in older people should be considered a disease or a part of the aging process is being debated, and some authors even describe xerosis as a low-grade atopic eczema. 24 Two methods are known for making artificial skin barrier-disrupted mouse models, namely, acetone application and tape-stripping. 19,21 Rissmann et al suggested that barrier disruption caused by acetone treatment is mainly caused by the removal of corneocytes, and it is also observed by tape-stripping.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 However, to understand the precise mecha- Atopic dermatitis in older patients represents a newly defined subgroup with complex and multifactorial etiology. 24 It is associated with various factors, including the aging process, skin dysbiosis, impaired sweat production, and differences in lifestyles. 27,28 SHE has been gaining attention recently for its various pharmacologic effects, including antioxidant and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Skin aging, depending on both chronological processes (intrinsic aging) and external factors (extrinsic aging), represents the most evident sign of human aging [ 16 , 17 ]. Intrinsic aging is a physiological process characterized by reduced cell proliferation in the basal layers and accumulation of senescent cells in the epidermis and dermis, characterized by skin dryness, thinning, fine wrinkles, xerosis, and itching, as well as susceptibility to several cutaneous disorders, including infections, autoimmune diseases, and tumors [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include Merkel cell precursors that may arise from epidermal stem cells or hair follicle stem cells, as well as pre-B cells, pro-B cells, or dermal fibroblast [2]. Risk factors for MCC development predominantly include exposure to ultraviolet (UV) light, advanced age, immune deficiencies, fair skin type, immunosenescence, the concurrent presence of other cancers, and chronic inflammation [1,3]. Two MCC types have been identified and classified based on specific molecular pathogenetic pathways related to mutational burden resulting from UV exposure and infection by the Merkel cell polyomavirus (MCPyV).…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%
“…Both UVassociated and viral-associated carcinogenesis lead to the development of highly immunogenic tumors due to the presence of multiple neoepitopes or viral proteins. These tumors are typically not clinically evident until they acquire immune escape mechanisms or when they are present in immunocompromised patients and cannot be effectively controlled by the immune system [3].…”
Section: Ultraviolet-related Merkel Cell Carcinomamentioning
confidence: 99%